Mechanisms of escape from the PGT128 family of anti-HIV broadly neutralizing antibodies. Issue 1 (December 2016) - Krumm, Stefanie; Mohammed, Hajer; Le, Khoa; Crispin, Max; Wrin, Terri; Poignard, Pascal; Burton, Dennis; Doores, Katie
Abstract Background Broadly neutralizing antibodies (bnAbs) directed against the mannose-patch on the HIV envelope glycoprotein gp120 have several features that make them desirable targets for vaccine design. The PGT125-131 bnAb family is of particular interest due to its superior breadth and potency. The overlapping epitopes recognized by this family are intricate and neutralization requires interaction with at least two N-linked glycans (N332/N334, N295 or N301) in addition to backbone-mediated contact with the323 IGDIR327 motif of the V3 loop. We have recently shown that this bnAb family consists of two distinct antibody classes that can bind alternate arrangements of glycans in the mannose-patch in the absence of N332 thereby limiting viral escape. This led us to further investigate viral resistance and escape mechanisms to the PGT125-131 bnAb family. Results Using an escape virus isolated from the PGT125-131 donor as a guide, we show that mutating both the V3 core protein epitope and repositioning critical N-linked glycosylation sites are required to restore neutralization sensitivity. Interestingly, neutralization sensitivity could be restored via different routes for the two distinct bnAb classes within the PGT125-131 family, which may have been important in generating the divergence in recognition. We demonstrate that the observed V3 mutations confer neutralization resistance in other virus strains through both gain-of-function and escape studies. Furthermore, we show that the V3 loop is important in facilitating promiscuous binding to glycans within the mannose-patch. Conclusions These data highlight the importance of the V3 loop in the design of immunogens aimed at inducing broad and potent bnAbs that can bind promiscuously to the mannose-patch.